Liraglutide Increases FGF-21 Activity and Insulin Sensitivity in High Fat Diet and Adiponectin Knockdown Induced Insulin Resistance - Yang, Mengliu; Zhang, Lili; Wang, Chong; Liu, Hua; Boden, Guenther; Yang, Gangyi; Li, Ling (PLOS ONE, 2012)
Background Liraglutide is a glucagon-like peptide-1 analogue that stimulates insulin secretion and improves β-cell function. However, it is not clear whether liraglutide achieves its glucose lowering effect only by its known effects or whether other as yet unknown mechanisms are involved. The aim of this study was to examine the effects of liraglutide on Fibroblast growth factor-21 (FGF-21) activity in High-fat diet (HFD) fed ApoE−/− mice with adiponectin (Acrp30) knockdown. Method HFD-fed ApoE−/− mice were treated with adenovirus vectors expressing shAcrp30 to produce insulin resistance. Hyperinsulinemic-euglycemic clamp studies were performed to evaluate insulin sensitivity of the mouse model. QRT-PCR and Western blot were used to measure the mRNA and protein expression of the target genes. Results The combination of HFD, ApoE deficiency, and hypoadiponectinemia resulted in an additive effect on insulin resistance. FGF-21 mRNA expressions in both liver and adipose tissues were significantly increased while FGF-21 receptor 1 (FGFR-1) and β-Klotho mRNA levels in adipose tissue, as well as FGFR-1-3 and β-Klotho mRNA levels in liver were significantly decreased in this model. Liraglutide treatment markedly improved insulin resistance and increased FGF-21 expression in liver and FGFR-3 in adipose tissue, restored β-Klotho mRNA expression in adipose tissue as well as FGFR-1-3, β-Klotho levels and phosphorylation of FGFR1 up to the levels observed in control mice in liver. Liraglutide treatment also further increased FGF-21 proteins in liver and plasma. In addition, as shown by hyperinsulinemic-euglycemic clamp, liraglutide treatment also markedly improved glucose metabolism and insulin sensitivity in these animals. Conclusion These findings demonstrate an additive effect of HFD, ApoE deficiency, and adiponectin knockdown on insulin resistance and unveil that the regulation of glucose metabolism and insulin sensitivity by liraglutide may be partly mediated via increased FGF-21 and its receptors action.